2018
DOI: 10.3389/fpubh.2018.00041
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Enhancement of Science Teachers’ Knowledge and Skills through Scientific Lecturing

Abstract: IntroductionDue to their importance in transmitting knowledge, teachers can play a crucial role in students’ scientific literacy acquisition and motivation to respond to ongoing and future economic and societal challenges. However, to conduct this task effectively, teachers need to continuously improve their knowledge, and for that, a periodic update is mandatory for actualization of scientific knowledge and skills. This work is based on the outcomes of an educational study implemented with science teachers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
3
5
0
2
Order By: Relevance
“…Linda believes that PBL is simply a methodology and anyone can teach it with a growth mind-set as well as a willingness to keep learning and updating their knowledge. This belief is consistent with a study by Azevedo and Duarte (2018). Linda told me that she kept a three-inch binder labeled by topics.…”
Section: My Reflection On Six Dilemmassupporting
confidence: 86%
“…Linda believes that PBL is simply a methodology and anyone can teach it with a growth mind-set as well as a willingness to keep learning and updating their knowledge. This belief is consistent with a study by Azevedo and Duarte (2018). Linda told me that she kept a three-inch binder labeled by topics.…”
Section: My Reflection On Six Dilemmassupporting
confidence: 86%
“…In the same way, the findings showed that continuing professional development significantly influences science curriculum implementation, which supplemented the existing literature of Marshall et al (2017) that teachers' involvement in a continuous professional development intervention is a pivotal step in implementing the science curriculum. The findings also affirmed Azevedo and Duarte's (2018) argument that providing quality in-service scientific lectures to teachers is critical to keep their skills, knowledge, and teaching practices current. The finding also supported Farrell's (2018) viewpoint that reflective activities help teachers improve their understanding of their instructional practices, become more proactive and confident when delivering lessons, and guide effective lesson planning and curriculum decision-making.…”
Section: Significance Of the Influence Of Pedagogical Content Knowled...supporting
confidence: 60%
“…Also teachers are not immune to alternative conceptions [ 116 ]. Before lessons, teachers should reflect on their own perceptions and check them with the help of several high-quality sources to identify deviations [ 118 ]. Holding alternative (non-scientific) conceptions, teachers possibly may not recognize them in their classroom [ 111 ] or even impart their own to their students.…”
Section: Discussionmentioning
confidence: 99%
“…If the responsibility is handed over to educators in different educational institutions, it must be ensured that they also have up-to-date scientifically sound conceptions about the subject matter, e . g ., through participation in training by experts or examination of reliable literature [ 118 ]. As conceptions on microplastics are mainly media-driven, teachers should regularly survey their students’ and their own conceptions [ 110 ].…”
Section: Discussionmentioning
confidence: 99%